Implementasi Chatbot Administrasi Akademik Berbasis Smojo.Ai pada Website Akademik STT Terpadu Nurul Fikri - Azizah Fatma Sunardi; Misna Asqia; Krisna Panji (LPPM STT Terpadu Nurul Fikri, 2026)
The focus of this final research is the development of a chatbot based on the Smojo.ai platform to facilitate academic services at STT Terpadu Nurul Fikri. The study is motivated by students’ difficulties in accessing academic and administrative information, such as slow responses from BAAK and the Finance Bureau, limited-service hours, and many repetitive questions. Therefore, an automated system that can provide fast and interactive services is needed. This research aims to identify obstacles in information access, develop the chatbot using the SDLC AGILE method, and analyze its effectiveness in supporting academic services. The SDLC AGILE stages include requirements analysis, design, implementation, testing (Black Box and Beta testing), and evaluation based on user feedback. Data were collected through interviews with staff and questionnaires given to students. The results show that the chatbot was successfully developed and integrated into the academic website. The chatbot provides information on administrative services at BAAK as well as procedures at the Finance Bureau, such as payment postponement and applying for clearance letters. The evaluation concludes that the chatbot is easy to use, responsive, and helps reduce staff workload. In conclusion, the chatbot based on Smojo.ai effectively improves the efficiency of academic services, especially in correspondence, and supports the digitalization of campus services.